2019
DOI: 10.1128/iai.00704-18
|View full text |Cite
|
Sign up to set email alerts
|

A Nonfimbrial Adhesin of Aggregatibacter actinomycetemcomitans Mediates Biofilm Biogenesis

Abstract: Periodontitis is an inflammatory disease caused by polymicrobial biofilms. The periodontal pathogen Aggregatibacter actinomycetemcomitans displays two proteinaceous surface structures, the fimbriae and the nonfimbrial extracellular matrix binding protein A (EmaA), as observed by electron microscopy. Fimbriae participate in biofilm biogenesis and the EmaA adhesins mediate collagen binding. However, in the absence of fimbriae, A. actinomycetemcomitans still retains the potential to form robust biofilms, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(73 citation statements)
references
References 62 publications
2
69
0
2
Order By: Relevance
“…In vitro studies indicate that A. actinomycetemcomitans binds in a linear fashion to salivary coated hydroxyapatite, shows minimal specificity, and thus never reaches a saturation point relative to surface binding [23,38]. Further, it has been shown that these fibrils provided a surface for glycoprotein and/or polysaccharide accumulation that also participates in the attachment process ( Figure 3) [27,39].…”
Section: Adherence Genes: Abiotic Adherencementioning
confidence: 99%
“…In vitro studies indicate that A. actinomycetemcomitans binds in a linear fashion to salivary coated hydroxyapatite, shows minimal specificity, and thus never reaches a saturation point relative to surface binding [23,38]. Further, it has been shown that these fibrils provided a surface for glycoprotein and/or polysaccharide accumulation that also participates in the attachment process ( Figure 3) [27,39].…”
Section: Adherence Genes: Abiotic Adherencementioning
confidence: 99%
“…Widespread colonization island or the tad locus [65] Autotransporter adhesins Aae, EmaA and Omp100/ApiA [66][67][68] A leukotoxin of the RTX family with specificity for leukocytes [69] Growth-inhibitory factor cytolethal distending toxin [70,71] CagE, capable of inducing apoptosis [72] Dispersin B, a biofilm-releasing beta-hexosaminidase [73] Vesicle-independent extracellular pelease of proinflammatory lipoprotein [74] The conspicuous growth in broth as small granules adhering to the walls of the test tube was specifically associated with rough colony variants [80]. Mutation analysis of the naturally competent strain D7S revealed flp-1, rcpA, rcpB, tadB, tadD, tadE and tadF to be indispensable for expression of fimbriae, while mutants of five other genes expressed reduced levels of fimbriae, or fimbriae that had different gross appearance [81].…”
Section: Referencesmentioning
confidence: 99%
“…Alternatively, these posttranslational modifications may contribute to the three‐dimensional folding of the adhesin to form the specific structures required for binding (Tang et al., 2012). Both fimbriae and nonfimbrial adhesins target either a single substrate or bind to multiple disparate macromolecules, as well as participating in biofilm formation and invasion of mammalian cells (Danforth et al., 2019; Fine et al., 1999,2005; Mintz, 2004).…”
Section: Introductionmentioning
confidence: 99%